Avanços e desafios da institucionalização da democracia participativa em Belo Horizonte a partir das conferências municipais de políticas para as mulheres realizadas no período de 2004 a 2010 - Oliveira, Girlene Galgani Reis de (2012)
This dissertation analyzes the social participation in the process of elaboration of policies at the Conferences of Public Policies held in Brazil principally on the Lula Government and more specifically from the case study of the Municipal Conferences of Policies for Women in Belo Horizonte. Among the various participatory institutions that guarantee the exercise of democracy, the Conferences of Public Policies are important instances of participation and deliberation, as they offer to the public the opportunity to directly intervene in governmental decisions, presenting guidelines for planning and public management according to the demands presented by different segments of Civil Society. They occur at specific intervals, usually every other year, and they seek the normative direction of thematic areas in Public Policy. The Conferences are organized at the three levels of government (municipal, state and national), and at each level the discussions of the problems perceived by the participants who elaborate proposals occurs, pointing the demands that are collectively approved. The Dissertation has the Municipal Conferences for Politics for Women of Belo Horizonte realized in 2004, 2007 and 2010 as focus and seeks to verify if in the understanding of the councilors of the Municipal Council of Women's Rights the proposals approved at these conferences were used as reference in the elaboration of Public Policies for the Municipal Health Area and if this participatory institution promoted the political and social inclusion of women in the city. Towards this goal, I addition to the relevant literature review, the research turned to documentary surveys and semi-structured interviews with counselors.